132k views
2 votes
Which is the solution for log(3x - 1) + log 2 = log 4 + log (x + 2) ?​

User Dipesh
by
4.7k points

2 Answers

2 votes

Answer:x=1

Explanation:

log(3x-1)+log2=log4+log(x+2)

log(2(3x-1))=log(4(x+2))

Cancel log on both sides

2(3x-1)=4(x+2)

Open brackets

6x-2=4x+8

Collect like terms

6x-4x=8+2

10x=10

Divide both sides by 10

10x/10=10/10

x=1

User PSchn
by
5.6k points
3 votes

Answer:

x=5

Explanation:

log(3x-1)+log2=log4+log(x+2)

log(2(3x-1))=log(4(x+2))

Cancel log on both sides

2(3x-1)=4(x+2)

Open brackets

6x-2=4x+8

Collect like terms

6x-4x=8+2

2x=10

Divide both sides by 2

2x/2=10/2

x=5

User AWhitford
by
5.8k points